PENGARUH LATIHAN BEBAN MELALUI METODE CIRCUIT TRAINING DAN SUPER SET TERHADAP PENURUNAN BERAT BADAN DAN PRESENTASE LEMAK PADA MEMBER EKA GYM SPORT CENTER - Faizal Eka Nugraha (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2022)
This study aims to find out the effect of Weight Training Through Circuit Training Methods and Super Set On Weight Loss and Fat Percentage In Eka Gym Sport Center Members. This research is a pre-experiment with the research design used, namely pretest-posttest. The results show that:(1) Exercise using circuit weight training methods has an effect on body weight before and after using the circuit weight training method by 9% and the percentage of fat before and after using the circuit weight training method by 36%. (2) Exercise using the super set method has an effect on body weight before and after using the super set method by 6% and the percentage of fat before and after using the super set method by 21%.(3) Circuit weight training method is more effective than the super set method for weight loss and fat percentage. This is evidenced by the percentage value in weight loss between circuit weight training method with super set method of 9% greater than 6% and the percentage value of fat percentage reduction between circuit weight training method with super set method of 36% greater than 21%.